2011
DOI: 10.1002/app.33689
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and properties of water‐borne polyurethane with branched straight aliphatic chains

Abstract: Water-borne polyurethane with branched straight aliphatic chains (CWPU) was prepared and characterized by FTIR and TEM. The relationship between structure and water-resistance of CWPU was studied. The results showed that the particle size of CWPU emulsion increases and the round particle turns into the spindleshaped particle with increasing of content of branched straight aliphatic chains. However, the particle size of CWPU emulsion is not sensitive to the increases of length of branched straight aliphatic cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 33 publications
(40 reference statements)
1
4
0
Order By: Relevance
“…The hydrophobic long aliphatic chain with a low polarity migrated easily to the surface of the WPU film, and thereby, the surface free energy of the WPU film decreased, and the film could not be easily wetted. This phenomenon was also reported in previous literature . The water absorption is an important parameter for the practical applications of a polymer.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…The hydrophobic long aliphatic chain with a low polarity migrated easily to the surface of the WPU film, and thereby, the surface free energy of the WPU film decreased, and the film could not be easily wetted. This phenomenon was also reported in previous literature . The water absorption is an important parameter for the practical applications of a polymer.…”
Section: Resultssupporting
confidence: 86%
“…It has been reported that the alkyl side groups in diols or polyols can improve the hydrophobicity and water resistance of WPUs . The side‐chain methyl group (CH 3 ), with its hydrophobic nature, can render a low surface tension to poly(propylene glycol) (PPG)‐based WPUs .…”
Section: Introductionmentioning
confidence: 99%
“…The regularity of the foam cell structure is reflected by plotting the distribution of the counted cell pore sizes. 38 The foam was evaluated for chemical structure by total reflection mode of Fourier transform infrared (FTIR) spectrometer at 500 ∼ 4000 cm −1 . FTIR spectra were collected by a Nexus 470 FTIR spectrometer (Nicolet, USA) in attenuated total reflectance mode with a subscale of 4 cm −1 and 16 scans for each sample.…”
Section: Experimental Sectionsmentioning
confidence: 99%
“…According to the order of adding a crosslinker, there are two main types of crosslinking modification: precrosslinking and postcrosslinking . Precrosslinking refers to the addition of multifunctional monomers to crosslink prepolymers during chain expansion or addition of polyfunctional chain extenders during polyurethane emulsification. , However, the main drawback of this modification method is that the viscosity of the prepolymer is too large in the synthesis process, and even a gel phenomenon occurs in some cases. Next, the prepolymer is difficult to disperse during emulsification, so it is difficult to obtain high solid content polyurethane emulsion. Typical WPU crosslinking agents for WPU include trimethylolpropane, ethylenediamine, etc.…”
Section: Introductionmentioning
confidence: 99%